Seeing design stances. Issue 1 (2nd April 2016) - Tenenberg, Josh; Socha, David; Roth, Wolff-Michael
Abstract: In this paper, we investigate the stances that designers take in relation to one another in design critiques. Analysis of audiovisual recordings of critiques between students and professional designers in industrial design in the DTRS 10 data-set reveals that design concepts not only are verbally narrated but also come to life in gesture, gaze, orientation and body movement. In these bodily performances, participants adopt and shift between several identified stances, which we call inscriptional, third - person, first - person and phenomenal . In social relations, these stances are mirrored, taken up, responded to and elaborated by the other participants. The critique itself, then, can be seen as a dialogical movement by the participating designers through a set of stances. By comparing a case in which participants are collocated to a case in which the participants are at a geographic distance facilitated only by real-time audio and shared computer display, we conjecture that this responsive mirroring and elaboration of stance can be hindered when participants do not have visual access to one another and thus increase the chances of communication breakdowns.